Transcriptome Analysis of Ostrinia furnacalis Female Pheromone Gland: Esters Biosynthesis and Requirement for Mating Success - Yao, Shuangyan; Zhou, Shuai; Li, Xiang; Liu, Xiaoguang; Zhao, Wenli; Wei, Jizhen; Du, Mengfang; An, Shiheng (Frontiers in Endocrinology, 2021)
Female moths use sex pheromones to attract males, and corresponding regulatory mechanism underlying sex pheromone biosynthesis is species-dependent. However, the detailed mechanism involved in sex pheromone biosynthesis in Ostrinia furnacalis has not yet been fully addressed. In the present study, transcriptome sequencing of O. furnacalis pheromone glands screened a serials of candidate genes involved in sex pheromone biosynthesis. Our analysis showed that sex pheromone release in O. furnacalis females arrives its peak at the 2nd scotophase, consistent with its mating behavior. Pheromone biosynthesis-activating neuropeptide (PBAN) was confirmed to regulate sex pheromone biosynthesis, and Ca2+ is the secondary messenger of PBAN signaling in O. furnacalis. The functional analysis of candidate genes demonstrated that the decreased mRNA levels or activities of calcineurin (CaN) and acetyl-CoA carboxylase (ACC) led to significant decrease in sex pheromone production and female capability to attract males, as demonstrated by RNAi-mediated knockdown and pharmacological inhibitor assay. Most importantly, the activities of CaN and ACC depend on the activation of PBAN/PBANR/Ca2+. Furthermore, fatty-acyl reductase 14 was involved in PBAN-mediated sex pheromone biosynthesis. Altogether, our results demonstrated that PBAN regulates sex pheromone biosynthesis through PBANR/Ca2+/CaN/ACC pathway to promote sex pheromone biosynthesis in O. furnacalis and provided a reference for non-model organism to study neuropeptide signal transduction.